About some infinite family of 2-bridge knots and 3-manifolds. (15th July 2000) - Kim, Yangkok
Abstract : We construct an infinite family of 3-manifolds and show that these manifolds have cyclically presented fundamental groups and are cyclic branched coverings of the 3-sphere branched over the 2-bridge knots( ℓ + 1 ) 2 or( ℓ + 1 ) 1, that are the closure of the rational( 2 ℓ − 1 ) / ( ℓ − 1 ) -tangles or( 2 ℓ − 1 ) / ℓ -tangles, respectively.